Influence of 17-alpha methyl testosterone on the production parameters of common carp (Cyprinus carpio L.) fry - Kovács, László; Simon, Ádám; Minya, Dániel; Homoki, Dávid; Kertész, Attila; Fehér, Milán; Stündl, László; Bársony, Péter (Acta Agraria Debreceniensis, 2018)
During our research we aimed at finding an answer as to what extent the different concentrations of 17-alpha methyl testosterone incorporated in the diet of common carp fries can influence the production parameters of the species, as well as how efficient their sexreversal can be with the use of this method. To this end, an aquarium experiment was conducted in the course of which four different hormone treatments were set and monitored. The fish feed was enriched with 17-alpha methyl testosterone in 50 ppm, 75 ppm, 100 ppm, 500 ppm dosages. The obtained figures revealed that the hormone treatments had no influence on the production parameters and conservation of the common carp fries. Further on, our team is to determine the sex of the fish through the examination of gonads during autopsy when they reach the 500 g average weight. Furthermore, a male specific test method which was supposed to be of great help in our attempt to select the sex-reversed specimens in the subsequent processes was also put to the trial. During the experiment the DNA-isolation of different sample types (muscle tissue, fin, mucus) of common carp with identified sex was successfully carried out. The extracted PCR product was examined with agarose gel. Our results indicated that the ccmf2 marker was applicable, however, the obtained figures were not reliable.